Oral manifestations of COVID-19 vaccinated individuals, post-infection, and different variants: a Brazilian population study - Larissa Di Carvalho MELO; Juliana Amorim dos SANTOS; Bruna Bastos SILVEIRA; Vitória Tavares de CASTRO; Ana Gabriela Costa NORMANDO; Ana Carolina PRADO-RIBEIRO; Alan Roger SANTOS-SILVA; Fabiana VARGAS-FERREIRA; Eliete Neves Silva GUERRA (Brazilian Oral Research)
Abstract This cross-sectional study aims to investigate the prevalence of oral manifestations in a sample of the Brazilian population with COVID-19. Adults diagnosed with COVID-19 through real-time PCR/serological tests were invited to participate. The online questionnaires were distributed at different times to analyze and compare SARS-CoV-2 variants considering the period of prevalence of these variants in Brazil. A total of 846 participants were included, of whom 539 were diagnosed before the Omicron variant. In total, 47.28% were vaccinated with at least two doses. The prevalence of oral manifestations was 52.6% (95%CI: 49.23–55.95), and the most common manifestations included taste disorder (38.06%; 95%CI: 34.85–41.38), xerostomia (17.61%; 95%CI: 15.19–20.32), and halitosis (11.58%; 95%CI: 9.59–13.92). The prevalence of persistent symptoms in post-COVID-19 was 12.1% (95%CI: 10.0–14.4) for taste disorder and 5.4% (95%CI: 4.1–7.1) for xerostomia. A significant association was found between females and persistent taste disorder (p = 0.0084) and oral manifestation and depression/anxiety (OR = 1.855, 95%CI: 1.267–2.717, p = 0.002), worse oral hygiene (OR = 1.729, 95%CI: 1.189–2.516, p = 0.004), and medication use (OR = 1.630, 95%CI: 1.123–2.367, p = 0.010) (p < 0.0001). In the Alpha, Beta, Gamma, and Delta variants, compared with the Omicron variant, taste disorder and xerostomia were less present when toothbrushing habits remained unchanged or improved (p < 0.0001). Oral manifestations in patients with COVID-19 were associated with depression/anxiety, worse oral hygiene, and medication, all of which reinforce its multifactorial etiopathogenesis.